Financial Performance Analysis of PT Adhi Kartiko Pratama Tbk in the Post-IPO Period Based on Financial Ratios - Syahid, Anida Almirah; Ananta, Anisah Nadya; Oehoedoe, Muhammad Sabrian; Shiddiq, Mohammad; Patmasari, Nur; Alamsyah R., Muh. Fajar (Westscience Press, 2026)
This study aims to analyze the financial performance of PT Adhi Kartiko Pratama Tbk in the post–Initial Public Offering (IPO) period based on financial ratios. The research employs a descriptive method with a quantitative approach, using secondary data derived from the company’s financial statements published on the Indonesia Stock Exchange. The analysis is conducted by calculating and interpreting liquidity, profitability, and solvency ratios to evaluate the company’s financial condition during its early stage as a public company. The results indicate a decline in liquidity and profitability, reflecting an adjustment phase in operational activities and asset utilization after the IPO. Meanwhile, solvency ratios show a relatively stable capital structure with a growing contribution of equity financing. These findings suggest that the financial performance of newly listed companies should be assessed by considering the transitional nature of the post-IPO period.